Development of a Family Engagement Measure for the Intensive Care Unit - Michael Goldfarb, MD, MSc; Sylvie Debigaré, MA; Nadine Foster, BN, RN; Nataliya Soboleva, MSc; France Desrochers, MSc; Laura Craigie, MSc; Karen E.A. Burns, MD, MSc (CJC Open, 2022)
Introduction: Family engagement is a goal of care delivery in the intensive care unit (ICU). However, currently, no validated instrument for the ICU is designed specifically to measure family engagement. Our objective was to develop a novel family engagement measure. Methods: The Family Engagement (FAME) tool was developed through an iterative process, with input from experts, family members, and end-users. The FAME questionnaire is composed of 12 items. Each item is scored using a 5-point Likert scale and transformed onto a 0-100-point range, with higher scores indicating greater engagement. We performed a single-site pilot study for family members of patients in a cardiovascular ICU. Results: The FAME tool had a high construct validity and required an average of 3.33 minutes to complete. A total of 32 family members completed the FAME questionnaire (mean age: 52.4 ± 14.2 years; 71.4% female; 47% adult child ; 31% spouse/partner). The overall mean FAME score was 84.0% ± 25.2%. Differences in engagement across various domains were identified. Conclusions: The FAME measure is a focused and pragmatic tool to measure the degree and type of family engagement in care of patients in the ICU. Further studies are needed to evaluate the FAME tool in a larger population. Résumé: Introduction: La participation de la famille est un objectif établi dans la prestation de soins dans les unités de soins intensifs (USI). Pourtant, il n’existe actuellement aucun instrument validé conçu précisément pour mesurer la participation des familles dans les USI. Notre objectif était d’élaborer une nouvelle façon de mesurer la participation des familles. Méthodologie: L’outil Family Engagement (FAME; participation de la famille) a été conçu par un processus itératif, avec la collaboration d’experts, de membres de familles et d’utilisateurs des services. Le questionnaire FAME comporte 12 éléments. Chaque élément est noté à l’aide d’une échelle de Likert en 5 points et transposé en un score de 0 à 100, un score plus élevé indiquant une plus grande participation. Nous avons réalisé une étude pilote dans un seul établissement auprès des membres de la famille de patients d’une USI en cardiologie. Résultats: L’outil FAME avait une bonne validité conceptuelle et nécessitait en moyenne 3,33 minutes à remplir. Au total, 32 membres de la famille ont rempli le questionnaire FAME (âge moyen : 52,4 ± 14,2 ans; 71,4 % de femmes; 47 % d’enfants adultes; 31 % de conjoints). Le score FAME moyen global a été de 84,0 % ± 25,2 %. Des différences quant à la participation aux divers volets ont été relevées. Conclusions: Le questionnaire FAME est un outil ciblé et pratique qui permet de mesurer le degré et le type de participation de la famille dans les soins des patients séjournant à l’USI. D’autres études doivent être menées pour évaluer l’outil FAME au sein d’une population élargie.